Analisis Manajemen Dana Bantuan Operasional Sekolah Dalam Meningkatkan Mutu Pembelajaran di SD Negeri 024772 Binjai - Mila Yanti Siregar (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to find out how the management of school operational assistance funds at SD Negeri 024772 Binjai. Sources of data came from school principals, supervisors, teachers and school committees at SD Negeri 024772 Binjai through interviews, documentation studies and observations. This study found that the School Operational Assistance (BOS) fund program was implemented in accordance with the provisions of the Minister of National Education Regulation Number 51 of 2011 concerning technical guidelines for the use of BOS funds and BOS financial reports. There is the participation of interested parties (school principals, parents of students, community leaders, education observers, the business world, and other members of the community) to contribute incentives in the management of BOS funds. Planning for the use of BOS funds at SD Negeri 024772 Binjai was carried out by compiling a RKTS. RKTS is a plan to obtain education funding from various sources of income as well as an annual work program composition consisting of a number of routine activities and several other activities accompanied by details of the financing plan in one fiscal year. Management of school operational funds at SD Negeri 024772 Binjai has been very effective in improving the quality of learning.